Macro and Micro Mineral Status of Feeds and Fodders of Chhattisgarh State - Goswami, Ajay; Garg, M. R.; Bhanderi, B. M. (Indian Journal of Animal Nutrition, 2017)
Feeds and fodder samples (n=358) were collected from 25 representative villages of the 9 districts of Chhattisgarh state to assess their status with regard to macro and micro minerals. Calcium content in wheat bran (0.20%), rice bran (0.15%) and broken rice (0.02%) was found to be below the critical level (0.30%). Phosphorus level in most of concentrate ingredients was high (0.26-1.04%) but low in dry roughages (0.07-0.12%). Feeds and fodder contained highly variable concentration of Mg (0.07-1.45%). Cereals straws were deficient in S (0.11%). Green fodders were not good sources of Cu (7.04 ppm). Paddy straw was low in Zn (27.00 ppm) but high in Mn (546.87 ppm) and Fe (402.87 ppm). Azolla green was found to be rich source of all the trace minerals. Selenium (0.63 ppm) was present in appreciable quantities in most of the feedstuffs. Rations of lactating cows were found to deficient in P, Cu, Zn and Co which were below the requirement of cows yielding 8 kg milk (4% fat) per day. Supplementing the deficient minerals through area specific mineral mixture could alleviate the deficiency of trace minerals in the state.